Generative AI literacy among pre-service teachers: Focusing on physical education majors - Lee, Yong-Jik; Jeong, Seung-Hoon (Journal of Education and e-Learning Research, 2026)
Generative artificial intelligence (GenAI) is transforming educational practice, yet limited research has examined how pre-service teachers in non-STEM disciplines are prepared to use it critically and pedagogically. This study investigated the level of GenAI literacy among pre-service teachers majoring in physical education in South Korea, where AI literacy is emphasized in national policy but unevenly implemented across disciplines. Using a descriptive survey design, students at a four-year university completed an online questionnaire during the fall semester of 2025. The survey, adapted from the Generative AI Literacy for Learning Scale, measured four dimensions: needs analysis, prompt and language skills, autonomous learning, and critical thinking. The results showed that participants demonstrated relatively strong competence in selecting appropriate AI tools and using GenAI for autonomous and collaborative learning. However, their perceived ability to critically evaluate AI-generated content, particularly in identifying bias and verifying information, was comparatively weaker. These findings suggest a gap between functional GenAI use and the evaluative and ethical reasoning required for responsible classroom integration. The study offers baseline evidence for developing discipline-sensitive GenAI literacy frameworks and highlights the need for teacher education programs to strengthen critical verification, bias awareness, and ethical decision-making.